PENGARUH KOMPENSASI DAN KESEHATAN DAN KESELAMATAN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA PT. INTAN SEJATI ANDALAN (ISA) DI KABUPATEN BENGKALIS - Sri Milawati; Zulfadil Zulfadil; Rosyetti Rosyetti (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The purpose of this study was to determine the effect of compensation and occupational health and safety on job satisfaction and its impact on employee performance.The population in this study were as big as 175 people, all permanent employees who work at PT. Intan Sejati Andalan.The sample is taken by using the proportional stratified sampling method by applying Slovin formula so that the sample size is as big as 122 employees. The collected data were analyzed by using SPSS Version 22. The results showed that compensation had a significant effect on employee performance, occupational health and safety. Furthermore compensation affects the performance through job satisfaction. This means that job satisfaction can mediate the effect of compensation on employee performance and occupational health and safety. This means that job satisfaction can also mediate the influence of occupational health and safety on employee performance.